Telehealth based parental support over 6 months improves physical activity and sleep quality in children with autism: a randomized controlled trial - Shen, Xin; Huang, Peiying; Liu, Qian; Guo, Yin; Zheng, Lan (Frontiers in Pediatrics, 2024)
Purpose: Sleep disturbances are prevalent in autistic children. The emergence of telehealth offers new possibilities for remote professional intervention. By combining telehealth with parental support, this study aims to explore a novel family-based model to enhance moderate-to-vigorous physical activity (MVPA) and improve sleep quality in children with autism. Methods: Thirty-four autistic children (mean age = 15.7 years) were randomly assigned to either a 6-month intervention group or a control group. Both groups received standard physical education classes at school. The intervention group received additional after-school telehealth support. MVPA and sleep quality were assessed one week before the intervention and at the six-month follow-up. Results: After six months, children in the intervention group nearly doubled their daily MVPA compared to the control group (Cohen's d = 8.34, CI95% = 6.17 to 10.52). Actigraphy-assessed sleep efficiency was notably higher (d = 2.35, CI95% = 1.44 to 3.26), and there were reductions in wake time (d = 1.65, CI95% = 0.84 to 2.46), sleep fragmentation (d = 0.80, CI95% = 0.07 to 1.52), and sleep latency (d = 0.82, CI95% = 0.09 to 1.54) were all reduced. These improvements in objective sleep metrics were corroborated by subjective assessments using the Sleep Disturbance Scale for Children (d = 0.86, CI95% = 0.13 to 1.59). Conclusions: Telehealth combined with parental support addresses barriers to enhancing health behaviors at home. This innovative model not only improves after-school MVPA and sleep quality in autistic children but also holds significant potential for benefiting other populations requiring remote support. (clinical registration: NCT06444659